FAKTOR USIA BERHUBUNGAN DENGAN KECEMASAN PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI: Age Factors Related to Anxiety in Breast Cancer Patients Undergoing Chemotherapy - Wike Rosalini; M.Elyas Arif Budiman (Forind Press, 2023)
Breast cancer is a disease caused by irregular division of body cells so that cell growth cannot be controlled and will grow into a tumor lump. The need for cancer therapy is increasing along with the increasing prevalence of breast cancer incidence. One of the effects of chemotherapy for breast cancer patients is anxiety. Anxiety is a vague fear and feelings of insecurity, isolation, helplessness, and uncertainty. This condition often arises due to a fear of imagining the side effects of chemotherapy and the future due to the disease will cause changes in his life. The purpose of this study was to determine the relationship with anxiety in breast cancer patients undergoing chemotherapy at Baladhika Husada Jember Hospital. The design used in this study was cross sectional. The population in this study was 311 people and the sample used was 76 people. The sampling technique used is probability sampling with a simple random sampling method. Based on the chi square test, it is known that the p<0.001 (p<0.05), meaning that there is a significant relationship between age and anxiety in breast cancer undergoing chemotherapy at Baladhika Husada Jember Hospital.